Pembelajaran Membaca Interpreatif dengan Pendekatan Cooperative Learning di Sekolah Dasar - Ahmad Ridhani Ar (Universitas Negeri Malang, 2016)
This study focuses on how to foster the learning of interpretative reading by using cooperative learning approach in the fifth grade of SDN Lowokwaru VI Malang. This is a collaborative action research using three cycles, involving 53 students. The results of the study reveal that to make the learning of interpretative reading by using cooperative learning approach in the fifth grade of SDN Lowokwaru VI Malang effective, the practitioners encourage the students schemata, divide the students into 8 groups, use their peers to understand the texts, share with them the content of the texts, revise the task, and respond to the whole process of learning.